RP-HPLC Method for Determination of Imeglimin Hydrochloride in Bulk and Tablet Formulation - Mubeen G; Navali, Sharanabasava; N, Lalitha (Asian Journal of Pharmaceutical Research and Development, 2024)
Imeglimin hydrochloride (IMEG.HCl) is a new tetrahydro triazine-containing class of oral antidiabeticagents referred to as ‘glimins’, is used to treat type 2 diabetes (T2D). It is the firstanti-diabetic drug of this type to receive approval. It is an inhibitor of oxidative phosphorrylation that also works to improve muscle glucose absorption and restore regular insulin secretion1. A reverse phase HPLC method was developed and validated for quantitative determination of Imeglininhydrochlorideusing a BRISA LC2 C18 (25 mm x 0.46 mm, 5µm) Column, isocratic mobile phase of Methanol: Phosphate buffer (10mM) pH6.0, at a flow rate of 1ml/min. The analyte was monitored at 243nm and retention time was found to be 3.097min.The peak obtained was symmetrical with tailing factor less than 2 and theoretical plates more than 2000. The developed HPLC method showed good linearity (R2=1), the intra- and inter-day precision was less than 2%, LOD and LOQ were 0.137 and 1.417 μg/ml andaccuracy for three different levels was found to be 101.23%w/w-100.83%w/w respectively.The method was validated in accordance with ICH guidelines Q2 (R1).2 and was found to be Specific, Accurate, Precise, Robust and can be successfully applied for routine analysis of Imeglininhydrochloridein bulk and in pharmaceutical dosage form.